Detection of DNA Polymorphism in Five Varieties of Rice in Tirunelveli District in India - J.A, De Britto; M, Yogaraj; N.N, Kumar (Malaysian Journal of Science, 2006)
In order to ascertain the genetic variability among five varieties of rice, Random Amplified Polymorphic DNA (RAPD) fingerprints were analyzed by Polymerase Chain Reaction (PCR) of genomic DNA using random primers. These primers produced multiple band profiles with a number of amplified DNA fragments varying from 5 to 13. A total of forty-three polymorphic bands were observed. The genetic distance between the population ranged from 0.2341 to 0.7885 and the genetic identity ranged from 0.4091 to 0.7865. The overall observed and effective number of alleles is about 2 and 1.15 respectively. Nei (1978) overall genetic diversity is 0.5108. It is clear that there is distinct genetic variability among the five varieties of rice. This information could be very valuable in the management of genetic resources in such economically important crop species.